Sosialisasi Pemberdayaan Tanaman Obat Keluarga (TOGA) Guna Meningkatkan Imunitas di Kala Pandemi - Diah Anugrah Dipuja; Atikah Nurhidayati; Farhan Maulana; Havira Salsabila; Janny Karina Ginting; Muhammad Albani; Muti Abdurrahman; Rian Dika; Risda Aulia; Suci Rahmadani; Tasya Putri Agyudia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
This article was prepared for aknowledging people for the medicine plant that can we found in our daily live. In Indonesia we usually named is as TOGA (Tanaman Obat Keluarga). Toga has a lot of advantages the most significant is this plant can help to decrease the mild symptoms of some diseases, but some people do not recognize this, especially in Desa Perhentian Luas Kecamatan Logas Tanah Darat. One of the reasons that we found why there still did not plant medicine plants in their environment is because of the lack of understanding they have. So, as a student college, we like to share our knowledge and we also bring some medical plant seeds. Like ginger, aloe vera, turmeric, greater galingale, kelor leaves, and temulawak. Our activity goes well and we wish that this will be a useful example for the resident in this village.